Inclusion of complexed trace minerals enhances performance of broiler chickens - Shemil P. Macelline; Peter H. Selle; Sonia Y. Liu; Lane Pineda; Yanming Han; Mehdi Toghyani (Journal of Applied Poultry Research, 2024)
SUMMARY: Trace minerals are essential components in standard broiler diets, playing a vital role in growth performance and skeletal development in broiler chickens. Conventionally, trace minerals have been included in broiler diets as inorganic salts. However, inorganic trace minerals are highly water soluble and reactive in the feed, thus, can potentially react with other dietary antagonists, such as phytate, fiber, and other minerals. This reduces their bioavailability for the birds. Alternatively, dietary trace minerals from complexed sources have displayed better stability and consequently bioavailability. The present study was completed to evaluate the efficacy of different sources and concentrations of zinc, manganese, and copper on growth performance, carcass parameters and tibia characteristics in broiler chickens reared to 35 d of age. There were 5 dietary treatments, including a control diet with ZnSO4, MnSO4, and CuSO4 as inorganic trace minerals, while the other 4 dietary treatments consisted of organic or hydroxychloride forms of Zn, Mn and Cu at different inclusion rates as complexed trace minerals. Diets supplemented with complexed trace minerals supported more efficient feed conversion than inorganic trace minerals from 1 to 35 d posthatch. Therefore, broilers offered diets with organic and hydroxychloride trace mineral blends exhibited improved FCR over inorganic trace minerals at notionally lower inclusion rates. Interestingly, complexed trace mineral inclusions at a lower level than those of inorganic sources did not result in any significant reduction in tibia breaking strength (P = 0.575), or toe ash (P = 0.406). This study shows that trace mineral supplementation as complexed sources in broiler diets exhibited superior efficacy than inorganic trace mineral sources as reflected in growth performance and tibia strengths.